Thin Capitalization Rules di Indonesia, Studi Kasus pada RS X - Sumayya Syahidah; Ning Rahayu (SUBSTANSI, 2018)
Abstract The aim of this research is to understand the impact on the implementation of Indonesian Minister of Finance Regulation Number 169/PMK.010/2015 about the Thin Capitalization Rules to the capital structure in RS “X”.This research is a case study on RS “X”, a hospital located on Mataram, West Nusa Tenggara. This research use secondary data from financial statement and Income Tax sheet with analytical technics used descriptive qualitative. In addition, primary data collected by interviews were also used in this study.The findings of this research founded RS “X” reported his financial statement in Debt to Equity ratio show 8:1. This number is greater than the standard that is stated in the PMK169. Most of the debt is caused by management which have to take working capital loans to the bank because the hospital lacks of funds to cover their operational costs for BPJS patients. This ratio causes that the loan expenses have to be corrected positively in income tax sheet. The amount of loan expenses that can deducted is Rp.807.685.185 and the rest Rp.1.009.606.481 have to be corrected as addition to taxable income. By doing this, the taxable income will increase Rp. 177,398,218.39.  The policy to reduce the ratio is to re-valuate the fixed assets so that it will add to the equity side, beside that the company should to carry out debt contracts to fund the needs of working capital with related parties, by then the debt will reclassified into shareholders' debt which according to the prevailing tax rules will be recognized as Equity. Keywords: DER, Income Taxes, Ministry of Finance Regulation, Thin-Capitalization Rules.